Nutritional profile of patients attended at the ambulatory of a private institution for trade workers in São Luís-MA - Mendes, Rakel de Sousa Oliveira (2020)
Introduction and objective: Due to the increased prevalence of Noncommunicable Chronic Diseases caused by the nutritional transition, the search for outpatient nutritional services has grown, helping to promote health and changing anthropometric parameters. The study aimed to identify the nutritional profile of patients treated at the outpatient clinic of a private institution focused on Trade Workers in São Luís-MA. Material and methods: This was a descriptive, cross-sectional study with secondary data collection, by collecting 90 medical records of patients treated at the outpatient clinic in 2018. Information was transcribed to a protocol with information on gender, age, marital status, weight, height, Body Mass Index (BMI), reason for seeking outpatient care, smoking, alcohol consumption, physical activity and associated pathologies. Data were analyzed using descriptive statistics. Results: There was a prevalence of female (84.4%), adult (96.7%), single (46.7%), non-smoking (91.1%) and alcohol (71.1%), and presence of physical activity (64.4%), mainly the practice of bodybuilding (67.2%). Among the minority who reported having some pathology, diseases related to the gastrointestinal tract were the most reported. Discussion: The prevalence of overweight patients (64.5%) was clear, confirming the large percentage obtained in relation to the search for nutritional care for weight loss (61.1%) and highlighting the nutritional transition experienced by Brazil. Conclusion: This study collaborated with the thematic approached contributing to the knowledge of the profile of the public served and, thus, a better outpatient care.